Effect of the width of cut tobacco on the quality of slim cigarette. Issue 6 (January 2021) - Zhao, Yunchuan; Zhang, Tao; Qiao, Xiaohui; Zhao, Jian; Hu, Qun; Feng, Hongtao; Yang, Lei; Wu, Jiacan; He, Xuefeng; Pu, Qian; Zhao, Meiwei; Qiu, Ye
Abstract: In order to further explore the characteristics of slim cigarette processing technology, this study designed different cut width (0.7mm and 0.8mm) of product A, and carried out the experiments of making and rolling under the same process conditions, and evaluated the influence of the width of cut tobacco on the quality of slim cigarette. The results showed that: the 0.7mm cut width has the following advantages: Processing characteristics, Short rejection rate, Reducing draw resistance, Weight stability, Uniformity of density is better than 0.8 mm cut width, and 0.7 mm cut width is more suitable for the production of slim cigarette.